Magnetic Resonance Imaging (MRI) Evaluation of Sellar Region Tumors with Histopathological Correlation (Bangladesh Medical Journal, 2021)
MRI is a complex, rapidly evolving modality which has assumed an increasingly important role in the diagnosis of Sellar region tumors. It is now the preferred modality for the definitive evaluation and follow-up of the most sellar region tumors. Using different pulse sequence small lesion can be detected even without contrast. Gd-DTPA provides valuable information in MR imaging sellar region tumors, particularly in pre-operative evaluation. This study was conducted to elucidate the accuracy of MRI in pre-operative evaluation of sellar region tumors and its validity by determining sensitivity, specificity, positive and negative predictive value with histopathological correlation. This cross sectional observational study was carried out in the department of radiology and imaging in collaboration with department of Neurosurgery, Dhaka Medical college Hospital, Dhaka during the period of January 2008 to April 2009. MRI of brain was done on 42 patients referred for evaluation of sellar region tumors. The following result and observation were obtained. The age range of the patient was 20 to 80 years. The mean age (HSE) was 34.31(+2.80). Maximum patients were in age group 20-30 years and male-female ratio was 1.8:1. Most sellar region tumor located in the intrasellar with suprasellar extension. Out of 42 patients 37 (88%) patients were truly diagnosed by MRI as sellar region tumors. The sensitivity of MRI to diagnosed macro adenoma was 81.25%, specificity 80.76%, positive predictive value 72.2%, negative predictive value 87.5%, accuracy 80.95%. This study finds that MRI is a valid imaging modality in the diagnosis of pituitary adenoma and sellar region tumor.Bangladesh Med J. 2020 Sept; 49(3) : 1-10